Growth and Yield of Corn with Different Animals Compost and Doses - Bambang Surya Adji Syahputra; Meriksa Sembiring; Riyanti; Nurhayati (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to determine of solid organic fertilizer (POP) from three animals’ feces namely cow, goat, and chicken were applied with various dosages in maize to increase growth and yield. The study was used RCBD factorial with three reps and POP type (K1 = chicken K2 = cow and K3 = goat) was the first factor and the POP doses (D0 = 0.00; D1 = 0.75; D2 = 0.150; D3 = 2.25 and D4 = 3.00/ plot) was the second factor. Parameters measured were plant height, number of leaves, stem diameter, leaf area, cob length, cob diameter, number of rows, and cob weight. The results were showed significantly different for the type of POP, where the chicken POP was significantly with cow and goat POP, but t between goat and cow POP was no significant differently. The dosage was found, significantly difference among doses, but interaction between the dosage with the POP was no significant difference, respectively. The results indicated that, various compost from feces cow, goat and chicken were increased growth and yield of corn, but the better compost feces chicken as compare those ones. Especially in dosage, whereas all dosage were providing positive impact in growth and yield, but dose 2.25kg/plot was given high in growth and yield of corn.